Strategies for neonatal developmental care and family-centered neonatal care - Hernández, Nasly Lorena; Rubio Grillo, María Helena; Lovera Montilla, Alexander (Investigacion y educacion en enfermeria, 2016)
To evaluate neonatal developmental care and family-centered care in a neonatal unit. Participatory action research with a purposive sample of health personnel and parents of hospitalized newborn in a Neonatal Unit in Valle del Cauca, Colombia. Five focal groups were conducted with seven mothers and 40 professionals of the unit team, and additionally, 24 non-participant observations were conducted about neonatal developmental care and family-centered care. Three strategies for promotion were implemented for both approaches and subsequently, results were evaluated in terms of practices that take place during neonatal care, after the intervention. A quantitative analysis with descriptive statistics and a qualitative content analysis were done to process the data. Three strategies were implemented: continuing education for professionals, allocation of materials for the positioning of the babies and an informative video for the parents about how the unit operates. The focus groups and the initial observation showed the necessity to enhance knowledge and practices of the personnel regarding neonatal developmental care and family-centered care. The promotion of neonatal developmental care and family-centered care generated positive changes in care practices of the professionals in the neonatal unit, through the use of education strategies, communication and the provision of positioning materials.